2021
DOI: 10.1017/s1754470x21000179
|View full text |Cite
|
Sign up to set email alerts
|

Stress and burnout in Improving Access to Psychological Therapies (IAPT) trainees: a systematic review

Abstract: For more than a decade, Improving Access to Psychological Therapies (IAPT) has been training a new workforce of psychological therapists. Despite evidence of stress and burnout both in trainee mental health professionals, and qualified IAPT clinicians, little is known about these topics in IAPT trainees. Consequently, this systematic review sought to establish the current state of the literature regarding stress and burnout in IAPT trainees. Electronic databases were searched to identify all published and avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Wisniewski & Torous 33 have proposed a new role within care teams called 'digital navigators' to reduce the time pressure on PWPs. This is particularly important considering that numerous studies have reported high rates of stress and burnout among PWPs, 34,35 which can lead to PWPs' avoidance of the patient-therapist alliance. 36 The digital navigator's role would involve setting up the programme, troubleshooting technological problems, reviewing patient data and producing data summaries, to provide PWPs with additional sights and time to effectively form a working alliance.…”
Section: Discussionmentioning
confidence: 99%
“…Wisniewski & Torous 33 have proposed a new role within care teams called 'digital navigators' to reduce the time pressure on PWPs. This is particularly important considering that numerous studies have reported high rates of stress and burnout among PWPs, 34,35 which can lead to PWPs' avoidance of the patient-therapist alliance. 36 The digital navigator's role would involve setting up the programme, troubleshooting technological problems, reviewing patient data and producing data summaries, to provide PWPs with additional sights and time to effectively form a working alliance.…”
Section: Discussionmentioning
confidence: 99%
“…Owen, J., Crouch-Read, L., Smith, M., & Fisher, P. (2021). Stress and burnout in Improving Access to Psychological Therapies (IAPT) trainees: a systematic review.…”
Section: Further Readingmentioning
confidence: 99%
“…A recent survey of UK psychological therapy practitioners also found evidence that lower workplace wellbeing was associated with a greater likelihood of wanting to leave the NHS, suggesting that workplace wellbeing may have an important relationship with high staff turnover in this population (Summers et al, 2020). Although research regarding trainee psychological therapists is comparatively scarce, existing evidence suggests that wellbeing may be further reduced during the training period, with trainees often reporting levels of stress and burnout that are greater than their qualified peers (Cushway, 1992;Cushway, 1997;Owen et al, 2021;Pakenham and Stafford-Brown, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations